Procédure méthodologique pour la remise en fonction de luminaires - Carole Maître (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A museum is frequently confronted with challenging issues concerning heritage collections whose conservation needs complete isolation while the diffusion of knowledge requires public exhibition. The operating of functional objects during exhibition is therefore problematic. This study proposes a methodology to guide the decision-making process for the exhibition of technical objects and to help defining the intervention which realize to operating the object, in accordance to the identified material risks, to the public safety, to the impact on the authenticity and value of cultural property, and finally, to the technological obsolescence.